Arquivo escolar: diagnóstico no arquivo do Colégio Paes de Carvalho - SOUSA, Milena Cristina Siqueira de (2017)
The paper aims to present a situational diagnosis of the accumulated documentary mass of the Paes de Carvalho State High School. Through a bibliographical survey on school archives and its relationship with archival theories, through a qualitative, exploratory research, and with the aid of a field research. Thus, direct research was used in the same place observing the work developed in the secretariat of the institution and its archival functions; Through an unstructured interview using as a tool a script with inquiring questions. Finally, through this work the lack of awareness by the managers and the main body and the demotivation and dissatisfaction on the part of the employees of this school and mainly the neglect with their documentary collection were observed.